To Romanize or not to Romanize?: Pashto language, social media and the global viability - Khan, Anoosh W. (The Journal of Humanities & Social Sciences, 2022)
Spoken language is one of the primary identity markers of an individual and/or a group. Language and its use demonstrate one’s ethnicity, profession, academic background, and social class among other identity markers. However, sometimes a contestation of sorts arises between the established spoken language and the written script especially when the written script is Romanized. Nowadays the Pashto script is popularly Romanized mainly when used as a medium of communication for short message service (SMS) and/or for responding on social media. This paper explores the evolution of Pashto script to understand the prospects of a language when the standard language is spoken but its written form is Romanized. In order to understand this contention I first establish how far informally Romanizing the Pashto script has popularized (or not) the usage of Pashto. Secondly, using Collier and Ong’s (2005) concept of ‘global assemblages’ I demonstrate the role of globalization in influencing the use of Romanized Pashto script. Thirdly, I explore the future of the Pashto script in terms of keeping the authentic language ‘alive.’ Finally, I conclude by stating that as we live in a globalized world therefore Romanizing a script can be a reason, a requirement, and perhaps an easily accessible way to keep not only a language but a culture alive locally, nationally, and internationally.